![](https://www1.michaeldemichele.com/img/nextpage1.png)
Suggested: sina-sinb/cosa+cosb+cosa-cosb/sina+sinb=0 - sina+sinb/cosa+cosb - prove that sin(a+b)=sina.cosb+cosa.sinb - cosa/sinb sinc+cosb/sinc sina+cosc/sinasinb=2 - (cosa+cosb)^2+(sina+sinb)^2=4cos^2(a-b/2) - sin(a+b)= sina*cosb + cosa*sinb - (cosa-cosb)^2+(sina-sinb)^2=4sin^2(a-b/2) - sina+sinb=2 then cosa+cosb= - sin2a-sin2b/sinacosa-sinbcosb=tan(a+b) - sina+sinb=a cosa+cosb=b - if sina/sinb=p and cosa/cosb=q - if 1/sina+1/cosa=1/sinb+1/cosb prove that cot(a/2+b/2)=tanatanb - sina cosb cosa+sinb cosc cosa+sinc cosacosb - sina/cosb.cosa+sinb/cosc.cosa+sinc/cosa.cosb=2 tana.tanb.tanc - sina+sinb cosa+cosb Browse related:
privacy contact
Copyright 2017 bapse
bapse is powered by Google and Youtube technologies
Thank you, for using bapse.
This site was designed and coded by Michael DeMichele,
and is being used as a portfolio demonstration. View more.